2′,7′-Dichlorofluorescein: Biological, Analytical, and Industrial Progress - Kousar, Shazia; Mudassir, Muhammad A.; Bibi, Fehmeeda; Irfan, Madiha; Alyas, Mohammad; Bukhari, Syed Waqas; Qadir, Salman (Mini-Reviews in Organic Chemistry, 2022)
Fluorescein derivatives have attracted a great deal of attention for ubiquitous applications on account of their unique properties. Particularly, the 2′,7′-dichlorofluorescein (DCF) is of paramount importance in biological, analytical, and industrial fields. Mainly, DCF has been employed as a reactant in reactive oxygen species (ROS) formation reactions in biological applications. It has been utilized in oxidative stress and cell spreading measurement. It has been extensively explored to analyze oxidative, respiratory burst, secretory peroxidase, and multidrug resistance-associated proteins (MRPs). It has been widely investigated for detecting/quantification of H2O2, glucose, lipid, cholesterol, other hydroperoxides, and polycationic protamine. Moreover, it has been applied to differentiate dopamine from ascorbic acid. It has also shown immense potential in biolabeling, cancer imaging, and drug delivery. Several studies demonstrated the great promise of DCF as a fluorescent probe for real-time monitoring/quantification of mercury, cadmium, zinc, arsenite, acetate, fluoride, thiocyanate, azide ions, hydrogen peroxide, ammonia, ozone, sulfur dioxide, and drug molecules. Furthermore, the use of DCF to manufacture dyesensitized solar cells and Schottky barrier devices opens up avenues for its industrial applications. Apart from presenting a comprehensive account of the immense potential of DCF in the areas mentioned above, the present review also intends to provide insight into its broader future scope for a myriad of applications to emerge.
Keywords: ROS formation